MEDIA SOSIAL SEBAGAI ALTERNATIF PENYIMPANAN ARSIP DIGITAL PRIBADI: Array - Gayatri Kusumawardani; Bening Tri Hanggoro (Arsip Nasional Republik Indonesia, 2018)
This paper focuses on personal digital records and their relation to social media as an alternative storage. Social media can be used as an alternative for digital personal files storage regardless their forms. The research method is literary study, combining primary and secondary data from archival and communication studies, and content analysis. Two important things of managing digital records are storage and back-up systems. There are three types of the repository: online, offline and nearline. The storage is a preliminary stage to developing digital records management.